Characterization of the "primary health care cascade" in public services in Mexico in localities with less than 100 000 inhabitants - M Arantxa Colchero; Rouselinne Gómez; Sergio Bautista-Arredondo (Instituto Nacional de Salud Pública, 2019)
Objective. To characterize the demand for public services among the population living in localities with less than 100 000 inhabitants. Materials and methods. We used data from the Encuesta Nacional de Salud y Nutrición (Ensanut) 2018. We characterize the primary health care cascade and estimated probit models on the probability of receiving care. Results. Among the population that reported a health problem, only 32% received care from a public institution. We found that women, having more than 50 years, being insured and belonging to the highest socioeconomic status -within this population- was associated with a greater probability of receiving care. Conclusions. Findings from this study show some of the challenges and opportunities to offer public health care services to the population that lives in more marginalized areas